FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN KONSUMEN PADA PT.TIKI JNE CABANG BENGKAYANG - Mar tono (Jurnal Ekonomi Integra, 2014)
Good service to the customer is very influential on consumer interest . Service is one of the important factors in realizing a company's goals , especially with regard to interest consumers to use products from a company . Therefore it is necessary to know the factors that influence the quality of Customer Service at PT . Tiki Janur Nugraha Ekakurir ( JNE ) Bengkayang Branch . In this study, researchers raised the question '' How to Influence Quality of Service provided by PT.Tiki Strip Ekakurir Nugraha ( JNE) Sub Agent Bengkayang To Consumers ? '' . The purpose of this study was to determine the effect of the quality of services provided by PT.Tiki Strip Ekakurir Nugraha ( JNE ) Sub Agent Bengkayang to consumers .In this study the authors use Descriptive Analysis Method with a number of sample population of 500 persons and 50 persons , data collection techniques using observation , interview , questionnaire and Documentary Studies and Literature .From the results the authors concluded that the study of Factors Affecting the Quality Customer Service On Line PT.Tiki Ekakurir Nugraha ( JNE ) is a branch Bengkayang consumer Assessment of aspects of supporting facilities at PT . Tiki Path Nugraha (  JNE ) Sub Agent Bengkayang is good . Consumers' assessment of the service aspect of PT . Tiki Path Nugraha ( JNE ) Sub Agent Bengkayang is pretty good . Consumer ratings of aspects of information on PT . Tiki Path Ekakurir Nugraha ( JNE ) Sub Agent Bengkayang is good . Consumers' assessment of service quality aspects of the PT . Tiki Path Ekakurir Nugraha ( JNE ) Sub Agent Bengkayang is pretty good . Consumer assessment of the safety aspects of the PT . Tiki Path Ekakurir Nugraha ( JNE ) Sub Agent Bengkayang is pretty good . Quality of Service provided by PT.Tiki Strip  Ekakurir Nugraha ( JNE ) Sub Agent Bengkayang positive effect on consumers